Co-Combustion Characteristics of Typical Biomass and Coal Blends by Thermogravimetric Analysis - Yuan, Ye; He, Yong; Tan, Jiaxin; Wang, Yongmeng; Kumar, Sunel; Wang, Zhihua (Frontiers in Energy Research, 2021)
In this study, the co-combustion characteristics of coal and biomass blends (20, 40, 60, 80, and 100 wt%) were investigated by thermogravimetric analysis. All the samples were operated under an oxidative atmosphere, with a heating rate of 20 C/min. The reaction stages, ignition and burnout temperature, maximum weight loss rate, and different combustion indices were determined. When the percentage of biomass in the blends was increased, the maximum mass loss rate was enhanced in the second region, and the ignition and burnout temperature was lowered, indicating the higher reactivity and better combustion performance of the samples. The comprehensive performance index presented an N shape with the increasing biomass blending ratio. Based on various combustion indices, 20% was an optimum percentage for the co-utilization of coal-biomass blends. A significant promoting interaction was observed between corn straw and rice straw blends, while inhibiting effects occurred between rice husk and coal. The kinetic parameters of the blends were evaluated by the Coats and Redfern method using the nth-order reaction model. The value of activation energy and the pre-exponential factor increased with the decreasing biomass percentage in the blends.